Purification of Antigen 85 Complex of Mycobacterium tuberculosis - Uma Ranganathan; Alamelu Raja (Bio-Protocol, 2013)
Serodiagnosis of tuberculosis using purified native antigens is one of the approaches for the early detection of TB. The Antigen 85 complex consisting of Ag 85A, 85B and 85C are the most abundant antigens in the culture supernatant of mycobacteria. It has also been shown to be the immunodominant (the property of an antigenic determinant that causes it to be responsible for the major immune response in a host) antigens of CFA (culture filtrate antigens – proteins secreted by mycobacteria into the culture medium). This protocol gives the details for purification of the Ag85 complex from CFA and also the method of isolation of the individual components of the complex by column chromatography.